Decision Model Support in Determining Outstanding Lecturer using Analytical Method Network Process - Karnita Afnisari; Indah Purnamasari (International Journal of Science, Engineering, and Information Technology, 2018)
Higher education is a subsystem that includes a program of national education diploma, bachelor, masters, specialist and doctoral degrees held by college. universities are obliged to provide education, research and community service. One element in the administration of higher education are the lecturer. Lecturers are academic personnel responsible for planning and executing the learning process, assess learning outcomes, conduct coaching and training, and conduct research and community service. Based on the Law of the Republic of Indonesia Number 14 Year 2005 on Teachers and Lecturers, Article 51 Paragraph (1) Item b, the professor is entitled to promotions and awards in accordance with academic performance. This study used the ANP method (Analytical Network Process). By using Superdecision software. The criteria used in this study is the teaching, research and community service. The results of this research is the relationship between teaching, research and community service related to the outstanding faculty in the election where the percentages in selecting outstanding faculty teaching performance at the first level = 22%, Personality = 18%, Teaching = 21%, 21% Research = , Devotion community = 16%.